2005
DOI: 10.17305/bjbms.2005.3277
|View full text |Cite
|
Sign up to set email alerts
|

Significantly Reduced Salivary Nitric Oxide Synthesis in Patients with Parkinson’s Disease

Abstract: In order to study concentration of nitric oxide (NO) in the saliva of patients with Parkinson's disease (PD), we measured the concentration of its stable metabolite nitrite (NO(2)-) in the saliva of these patients and healthy subjects. We analyzed saliva flow rate and salivary NO concentrations in 16 subjects with Parkinson's disease and in 16 healthy subjects. Concentration of nitrite was determined by colorimetric method using Griess reaction. Saliva flow rate was significantly lower in patients with Parkins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Further experimentation will determine whether high‐throughput ELISA for salivary HO‐1 in PD and other conditions will necessitate concomitant measurement of AMY1A protein. Hyper‐ or hyposialorrhea may arise in PD individuals as autonomic nervous system manifestations of the disease attributed to uncoordinated deglutition and pooling of saliva within the oropharynx and following treatment with pro‐DA or anticholinergic medications . Though no correlations have been reported between hyper‐ or hyposialorrhea and salivary biomarker levels, future studies of HO‐1 as a potential biomarker for idiopathic PD should assess whether these levels are affected by salivary secretion rates.…”
Section: Discussionmentioning
confidence: 99%
“…Further experimentation will determine whether high‐throughput ELISA for salivary HO‐1 in PD and other conditions will necessitate concomitant measurement of AMY1A protein. Hyper‐ or hyposialorrhea may arise in PD individuals as autonomic nervous system manifestations of the disease attributed to uncoordinated deglutition and pooling of saliva within the oropharynx and following treatment with pro‐DA or anticholinergic medications . Though no correlations have been reported between hyper‐ or hyposialorrhea and salivary biomarker levels, future studies of HO‐1 as a potential biomarker for idiopathic PD should assess whether these levels are affected by salivary secretion rates.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, NO levels in PD are ambiguous and studies on nitrite and nitrate measurements in the cerebrospinal fluid (CSF) of PD patients have been contradictory, as there was no change [ 37 ], increase [ 38 ] or decrease [ 39 , 40 ]. On the other hand, some studies have shown that CSF and plasma nitrate levels did not correlate with age at onset, duration, scores of the unified Parkinson’s disease rating scales, and Hoehn and Yahr staging in the patients group [ 37 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Huerta et al found no association among PD and three polymorphisms in the eNOS, nNOS and iNOS genes ( 38 ). Furthermore, significantly low circulating levels of NO and reduced salivary NOS were demonstrated in patients with PD ( 39 , 40 ). Chronic administration of rotenone was found to increase the NO levels in the cortex and striatum of rats, leading to significant injury in the nigrostriatal pathway ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%